Modelo Gerencial Para La InnovaciF3;n En La GestiF3;n De Las Organizaciones Educativas Del Sector PFA;blico. Un Enfoque Desde El Desarrollo Humano (Global Journal of Human-Social Science, 2022)
The study aims to analyze the management models that prevail in the management of educational organizations in the public sector considering the human development approach starting from the postulates of Aguilar 2015 Aranguren 2016 Ochoa Serna and D az 2014 Marco Loguzzo and Fedi 2016 Flores 2010 among others It is a interpretive qualitative ethnographic study taking as informants key directors of the educational institutions of the public sector of the Circuit 2 of the Maracaibo municipality The techniques of observation and interview making a content analysis with the hermeneutical method The results indicate that in these selected organizations there is relevance to the guidelines and regulations issued by the Ministry of Education taking into account the results without specifying that the processes are not met efficiently and effectively because they are not provided importance to the staff in terms of their human development without considering their talents and skills as well as permanent training is not provided to carry out its functions generating a management with an emphasis on what is administrative It is concluded that according to the findings obtained from the interpretation of the answers the managerial model that prevails in the educational organizations of the public sector is the bureaucratic without giving relevance to human development
Keywords: modelos gerenciales; gestiF3; n; organizaciones educativas; sector pFA; blico